2021
DOI: 10.1177/03000605211065388
|View full text |Cite
|
Sign up to set email alerts
|

1470 nm/980 nm dual-wavelength laser is safe and efficient for the en-bloc resection of non-muscle invasive bladder cancer: A propensity score-matched analysis

Abstract: Objective To evaluate the efficacy and safety of a 1470 nm/980 nm dual-wavelength laser system used for the en-bloc resection of non-muscle invasive bladder cancer (NMIBC) compared with transurethral resection of bladder tumour (TURBT). Methods This retrospective study analysed the demographic and clinical data from patients diagnosed with NMIBC that were treated by either dual laser or TURBT. Intraoperative characteristics, postoperative characteristics and outcomes between the two groups were compared. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that ERBT offers better pathological analysis and oncological outcomes (3-6). Thulium and holmium are the most frequently used lasers for this procedure, with the hybrid laser being a new addition that combines thulium and diode to improve hemostatic properties (5,(7)(8)(9). Objective: This report aims to discuss the use of two types of lasers, hybrid and holmium, for ERBT.…”
mentioning
confidence: 99%
“…Recent studies have shown that ERBT offers better pathological analysis and oncological outcomes (3-6). Thulium and holmium are the most frequently used lasers for this procedure, with the hybrid laser being a new addition that combines thulium and diode to improve hemostatic properties (5,(7)(8)(9). Objective: This report aims to discuss the use of two types of lasers, hybrid and holmium, for ERBT.…”
mentioning
confidence: 99%